The Quantity of Metal Elements in Sand of Mai Khao Beach Phuket Province - Suteerasak, Thongchai; Limsakul, Wadcharawadee; Koedsin, Werapong; Tanchana, Sirirat; Chongsrirattanakun, Wiangchai (Burapha Science Journal, 2026)
Proportion of grain size of sand and metal quantity (Al, Fe, Mg, Sr, Ti, Rb, Cu, Cr, Mn, Pb and Zn) in sand on Mai Khao beach, Phuket Province were studied to present the persistence of such metals in sand, which was the habitat of marine benthos. This study was very important, because some marine benthos such as mole crabs were found in only Mai Khao beach area. The results obtained showed the environment that was suitable for such a marine benthos. Trace elements (Cu, Cr, Mn, Pb and Zn) were analyzed by geochemistry method, whereas main elements (Al, Fe, Mg, Sr, Ti and Rb) were analyzed using X-ray Fluorescence Spectrometry (XRF). The results showed that sand particles with a size of more than 250 microns were found in the largest portion. Fine sand and very fine sand were found in moderate and the smallest portions, respectively. Moreover, main element quantities were found to be Al > Fe > Mg > Sr > Ti > Rb, whereas trace element quantities were found to be Cu > Mn > Zn > Cr. However, Pb was in least amount, then it could not be detected by Inductively Coupled Plasma Optical Emission Spectrometer (ICP-OES). In addition, Cu was found in only one station from total 10 sampling stations, and the amount of Cu was found to be 88.1 mg/kg, which was higher than that stated for standard value (< 21.5 mg/kg). Nevertheless, other metals in sand were assumed that they were in the sand, which came from the decay of natural substances on land and some had been blown up from the ocean in the past.